Exports: Orientation towards emerging markets - Marius Clemens; Florian Mölders; Dieter Schumacher (DIW Economic Bulletin, 2011)
Nearly 60 percent of globally traded industrial goods are R&D-intensive. Two fifths are goods with very high research intensity (cutting-edge technology), while the remaining three fifths are goods with high research intensity (high-level technology).1 Up until the 1990s, the USA was the global market leader. However, since then, the situation has changed in favor of Germany and remained so despite the recent economic crisis.2 In 2009, Germany exported R&D-intensive goods amounting to USD 670 billion. The two main competitors, the USA and Japan, exported goods worth USD 561 and 388 billion respectively. The new Central and Eastern European EU member states, which increasingly focus on the production of R&D-intensive goods, reached a value of USD 189 billion altogether. The situation on the import side is reversed: Here the US market dominates with imports worth USD 756 billion, while Germany comes second with USD 430 Billion.
Keywords: F10; F14; O14; 330; international trade; country and industry studies of trade; manufacturing industries